The effect of vaginal progesterone on Doppler findings in increased uterine artery resistance. (18th August 2021) - Jamal, Ashraf; Moshfeghi, Maryam; Molaei, Behnaz; Moradi, Yousef; Hashemi, Neda
Abstract: Objective: The present study aimed to evaluate the effect of vaginal progesterone on Doppler finding in increased uterine artery resistance compared with aspirin. Materials and methods: This study is a double-blind randomized clinical trial that was conducted on 140 pregnant women with increased uterine artery resistance who were referred to the Shariati hospital (Tehran, Iran) in 2017–2018. Patients were randomized to 1 of the 3 treatment groups – group A: tablet aspirin 80 mg; group B: vaginal suppository progesterone; and group C: control group without any intervention. Low-risk pregnant women at the gestational age of 16–20 weeks, were assessed by the uterine artery Doppler. In the presence of increased resistance of the uterine artery, patients were randomly assigned to one of the three above mentioned groups. Results: The results of paired t -tests for right uterine artery pulsatility index (RUA.PI), right uterine artery resistance index (RUA.RI), left uterine artery PI (LUA.PI), and left uterine artery RI (LUA.RI) before and after of intervention in the three groups were statistically significant. Also, the one-way analysis of variance (ANOVA) results for comparison between three groups showed that before the intervention only means of RUA.PI has a significant difference between three groups ( p = .025), but means of all variables after intervention shows a significant difference ( p < .001). Conclusion: The findings showed that the use of vaginal progesterone suppressed the resistance of uterine artery compared to aspirin.